Densities and Refractive Indices for N-Arylhydroxamic Acids in Dimethylsulphoxide at Various Temperatures - Verma, V.; Pande, R. (Asian Journal of Chemistry, 2013)
Refractive index deviations (nE), excess volumes (VE) and molar refraction (RM) of two isomeric hydroxamic acids, N-phenyl-2-methylbenzohydroxamic acid, N-phenyl-2-nitrobenzohydroxamic acid and N-phenyl-3-nitrobenzohydroxamic acid have been calculated from experimental data of refractive indices (n) and densities (r) in dimethyl sulphoxide at various temperatures (298.15, 303.15, 308.15 and 313.15) K. Results obtained have been discussed in terms of intermolecular ineteractions and a comprehensive discussion has been provided. The apparent molar volume at infinite dilution and the slope of Masson's equation are computed, to interpret the solute-solvent interaction.